Cellulose Nanoparticles as Controlled Release Nanocarriers for Urea - Kimberly Tay, Wei Wei; Chin, Suk Fun; Mohd Effendi, Wasli (Springer Nature B.V., 2025)
Purpose Conventional fertilization raises several environmental issues. Utilizing cellulose from paper waste presents a promising opportunity to create biodegradable cellulose nanoparticles, which can serve as controlled-release nanocarriers for urea, contributing to sustainable agriculture. Methods Cellulose nanoparticles of various mean particle sizes were synthesized from cellulose fibers derived from paper wastes by using the nanoprecipitation method. The fertilizer release characteristics of cellulose nanoparticles were evaluated using urea as the model fertilizer at room temperature. The release kinetic profiles of urea from cellulose nanoparticles were analyzed in both soil and water environments. Results The loading capacity of urea into cellulose nanoparticles was profoundly affected by factors such as mean particle sizes and the conditions of the release media. The highest loading capacity is found in cellulose nanoparticles of 30.54 nm with 173.85 mg/g. The urea loading capacity can be enhanced by optimizing the synthesis conditions of cellulose nanoparticles including cellulose concentrations, the addition of Tween 80 and the volume of precipitating medium. The urea release kinetics from cellulose nanoparticles can be adjusted by using cellulose nanoparticles with different average particle sizes. Conclusion Optimized cellulose nanoparticles made from cellulose derived from paper waste have the potential to serve as cost-effective controlled-release fertilizer nanocarriers